The Correlation Between Students’ Anxiety and Learning Activity towards Their Speaking Ability - Mira Listia Julianingsih (Journal of Languages and Language Teaching, 2018)
This research was aimed to know the correlation  between students’ anxiety and learning activity towards their speaking ability at tSMAN 01 Jereweh in academic year 2016/2017. This research was correlation research The sample of the research was all of the second grade students of SMAN 01 Jereweh in academic year 2016-2017 which consists of one class. One class was 28 students. The data was collected by using questionnaire  to collected the data of students’  learning activity  and  their anxiety meanwhile  test to know student speaking ability speaking test was administered.  The  data  was  analyzed  by using person product moment,  multiple linear regression and multiple correlation. From the data analysis, it was found that the result of correlation score r=0.687. It means the correlation between both of variable   and Y in moderate correlation because “r” score not close enough to +1. And the significant score f=9,523 it mean f=test > f-table of on degree of freedom of 25. Based on the result of the study, in can be concluded there is the the correlation  between students’anxiety and learning activity towards their speaking ability  at the second grade student of SMAN 01 Jereweh in academic year 2016/2017. It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.